Classics from this journal: Martin Rudwick’s ‘The Emergence of a Visual Language for Geological Science 1760–1840’, History of Science, xiv: 3, 1976, pp. 149–95. - Kusukawa, Sachiko (History of Science, 2016)
This is a brief review of the significance of Martin Rudwick’s article, ‘The Emergence of a Visual Language for Geological Science 1760–1840’, published in this journal 40 years ago.